Analysis of the English language teaching system in the Ecuadorian air force headquarters in connection with the six curriculum components - Batallas Lara, Cosme Felipe (2006)
Ecuadorian Air Force Headquarters is carried out regular English language courses approximately 20 years ago, with an average of 40 students for level and 120 students for each academic year, in levels like: basic, intermediate and advanced with a total of 2400 students until now approximately, using a methodology that satisfy partially the requirements of the six curriculum components like: objectives, contents, time, methodology, didactic resources, and evaluation. Although it is certain that the diagnostic survey doesn't define a specific problem, in general form, we observe the existence of a few inconveniences that added configure a bigger problem. This is the reason which it is necessary to carry out an analysis of the teaching system of this language in the Air Force Headquarters1 that has for purpose to determine the execution level in the application of the six curricular components, the mistakes that exist, and the effect of this in the achievement of the target goals and from this analysis, to design an alternative proposal. Taking into account that today in the XXI century in a completely interconnected world, the English language constitutes a fundamental tool of communication in the whole planet. English is the main vehicle of the process of globalization of the knowledge and it has become an essential factor of the academic formation into the professional-military field development.